Frequency of IRF5+ dendritic cells is associated with the TLR7-induced inflammatory cytokine response in SARS-CoV-2 infection - Cords, Leon; Woost, Robin; Kummer, Silke; Brehm, Thomas T.; Kluge, Stefan; Schmiedel, Stefan; Jordan, Sabine; Lohse, Ansgar W.; Altfeld, Marcus; Addo, Marylyn M.; Schulze zur Wiesch, Julian; Beisel, Claudia (Cytokine, 2023)
The SARS-CoV-2 infection leads to enhanced inflammation driven by innate immune responses. Upon TLR7 stimulation, dendritic cells (DC) mediate the production of inflammatory cytokines, and in particular of type I interferons (IFN). Especially in DCs, IRF5 is a key transcription factor that regulates pathogen-induced immune responses via activation of the MyD88-dependent TLR signaling pathway. In the current study, the frequencies of IRF5+ DCs and the association with innate cytokine responses in SARS-CoV-2 infected individuals with different disease courses were investigated. In addition to a decreased number of mDC and pDC subsets, we could show reduced relative IRF5+ frequencies in mDCs of SARS-CoV-2 infected individuals compared with healthy donors. Functionally, mDCs of COVID-19 patients produced lower levels of IL-6 in response to in vitro TLR7 stimulation. IRF5+ mDCs more frequently produced IL-6 and TNF-α compared to their IRF5− counterparts upon TLR7 ligation. The correlation of IRF5+ mDCs with the frequencies of IL-6 and TNF-α producing mDCs were indicators for a role of IRF5 in the regulation of cytokine responses in mDCs. In conclusion, our data provide further insights into the underlying mechanisms of TLR7-dependent immune dysfunction and identify IRF5 as a potential immunomodulatory target in SARS-CoV-2 infection.